Our future inheritance. Issue 2 (July 1975) - Short, R V
Abstract : Two of the most important topics in the field of medical ethics today are insemination by donor (AID) and in-vitro fertilization. The conclusions of a working party set up by the British Association for the Advancement of Science are embodied in a small book reviewed on pate 108 of this issue, but we feel that more discussion than can be set out in the space allocated to book reviews is justified. Also, this journal in its first number has already devoted a group of papers to the issue of abortion, so the conclusions of the working party and our own comments overlap and we hope illuminate further the problems enunciated.